Managing Personal Finance: The Role of Spiritual and Financial Knowledge - Putu Atim Purwaningrat; Luh Nik Oktarini; Ida Ayu Anggawulan Saraswathi (Warmadewa Management and Business Journal (WMBJ), 2019)
Managing personal finance (financial management behaviour) is a person's expertise in arranging, planning, budgeting, checking, managing, controlling, searching and storing daily financial funds. Spiritual intelligence and financial knowledge have relevancy in influencing financial management. This study aims to find out how the influence of spiritual intelligence and financial knowledge on personal financial management in Students of the Faculty of Economics, Business, and Tourism, University of Indonesia Hindu. The research sample was 100 people by using the simple random sampling method. The results of data analysis based on multiple linear regression test found that partially spiritual intelligence has positive implications for the management of personal finance. Financial knowledge variables have positive implications for managing personal finance.